Learning innovation through developing interpreter book: a classroom interpreting practice - Afif Suaidi; Abdul Gafur Marzuki; Anita Anita; Villy Al Viyani; Erizar Erizar (JINoP (Jurnal Inovasi Pembelajaran), 2025)
In today's rapidly evolving educational landscape, innovative approaches are increasingly needed to enhance learning and address specific challenges, such as the effective teaching of interpreting skills for students studying translation and interpreting. This research aims to enhance the quality of an interpreter book for classroom use by employing a qualitative R&D approach using the ADDIE model, focusing on interpreting practice among sixth-semester students at the English Education Department. The research results show that the initial design of the interpreter book focused on offering students interpreting study and practice, developed from three resource books. Students evaluated the book using a 1-4 rating scale, and a need analysis was conducted with fourth-semester students to gather additional insights. The redesign phase added descriptions of proper and inverse interpreting based on evaluation and need analysis data. This reevaluation led to the inclusion of new features like illustrations, YouTube links, and texts in the book. The research applied the ADDIE model in seven steps, including two rounds of design and development. The initial design focused on developing interpreting skills like listening, note-taking, and clear expression, with sequential instruction in various interpreting modes. The second round of design and development further refined these aspects.